Análisis termogravimétrico del cartílago articular de ratones ejercitados después de inmovilización - Ozaki, Guilherme Akio Tamura [UNESP]; Kodama, Fábio Yoshikazu; Camargo, Regina Celi Trindade [UNESP]; Job, Aldo Eloizo [UNESP]; Koike, Tatiana Emy [UNESP]; Watanabe, Adriana Yukie; Camargo Filho, José Carlos Silva [UNESP] (FapUNIFESP (SciELO), 2015)
Introduction: Joint immobilization is a technique often used in orthopedic treatment and, associated with the aging process, promotes changes in both the structure and synthesis and biomechanics of cartilage tissue. Objective: To describe the effects of immobilization, free remobilization and remobilization by physical exercise over articular cartilage of rats of two age groups. Methods: Thirty nine Wistar rats divided into two groups according to age, an adult group (five months old) and an elderly group (15 months old), and subdivided into: control, immobilized, free remobilized and remobilized by physical exercise. The pelvic limb of rats was immobilized for seven days. The exercise protocol consisted of 25 minutes swimming sessions, five sessions per day. The hip articular cartilage was subjected to thermogravimetric analysis, and the water content was evaluated. Results: In adult animals immobilization reduced the water content of the articular cartilage, and the remobilization protocols were effective to restore the initial condition of the tissue. In elderly animals there were not significant differences among the groups, however the elderly control group obtained results significantly lower than the adult control group (X: 13.10 ± 5.24 vs 10.70 ± 1.95). Conclusions: Immobilization and the senescence process induce the decrease of water content of articular cartilage and remobilization protocols were effective to restoring this property only in adult animals.
Análise termogravimétrica da cartilagem articular de ratos exercitados após imobilização
Thermogravimetric analysis of articular cartilage of exercised rats after immobilization
Keywords: Age factors; Swimming; Thermogravimetry